Over 70 % Faradaic Efficiency for CO2 Electroreduction to Ethanol Enabled by Potassium Dopant‐Tuned Interaction between Copper Sites and Intermediates. (28th July 2022) - Ding, Lianchun; Zhu, Nannan; Hu, Yan; Chen, Zheng; Song, Pin; Sheng, Tian; Wu, Zhengcui; Xiong, Yujie
Abstract: It is highly desired yet challenging to steer the CO2 electroreduction reaction (CO2 ER) toward ethanol with high selectivity, for which the evolution of reaction intermediates on catalytically active sites holds the key. Herein, we report that K doping in Cu2 Se nanosheets array on Cu foam serves as a versatile way to tune the interaction between Cu sites and reaction intermediates in CO2 ER, enabling highly selective production of ethanol. As revealed by characterization and simulation, the electron transfer from K to Se can stabilize Cu I species which facilitate the adsorption of linear *COL and bridge *COB intermediates to promote C−C coupling during CO2 ER. As a result, the optimized K11.2% ‐Cu2 Se nanosheets array can catalyze CO2 ER to ethanol as a single liquid product with high selectivity in a potential area from −0.6 to −1.2 V. Notably, it offers a Faradaic efficiency of 70.3 % for ethanol production at −0.8 V with as is stable for 130 h. Abstract : Potassium doping of Cu2 Se nanosheet arrays on copper foam serves as a versatile method for tuning the interaction between Cu sites and reaction intermediates. This approach enables CO2 electroreduction to ethanol as a single liquid product with a high Faradaic efficiency (FE) of 70.3 % and an extraordinary stability for 130 h at −0.8 V.